Transforming TPACK of elementary school teachers: The role of training based on collaboration, practice, and reflection - Ai Hayati Rahayu; Ari Widodo; Udin Syaefudin Saud; Muslim (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
Integrating technology into the learning process requires teachers to possess strong Technological Pedagogical Content Knowledge (TPACK). This study examines the impact of a training approach based on collaboration, practice, and reflection in enhancing elementary school teachers' TPACK and teaching abilities. The research employs a mixed-methods approach with an embedded experimental design. The training participants, totaling 84 individuals, were randomly divided into experimental and control groups, with the subjects participating in a training program designed to promote teacher collaboration, provide hands-on practice experiences, and integrate reflective learning. The instruments include a TPACK questionnaire, lesson plan (RPP) observation sheets, and classroom teaching practice observation sheets. Data analysis was conducted using difference tests and correlation tests. The findings reveal that this training approach significantly improved teachers' understanding and application of TPACK in classroom learning contexts. There was a significant difference in TPACK knowledge between participants in the experimental group and those in the control group. Additionally, this study emphasizes the importance of reflective practice in strengthening the integration of technology, pedagogy, and content knowledge. These findings provide valuable insights for designing professional development programs for educators to effectively enhance their technological and pedagogical competencies.